A review of early displaced maxillary canines: Etiology, diagnosis and interceptive treatment - ACAR, ZEYNEP AHÜ (My University, 2011)
Impaction of maxillary canines is a frequently encountered clinical problem the treatment of which usually requires an interdisciplinary approach. Surgical exposure of the impacted tooth and the complex orthodontic mechanisms that are applied to align the tooth into the arch may lead to varying amounts of damage to the supporting structures of the tooth, not to mention the long treatment duration and the financial burden to the patient. Hence, it seems worthwhile to focus on the means of early diagnosis and interception of this clinical situation. In the present article, theories related with the etiology of impacted canines and predictive variables of canine impaction in the mixed dentition are reviewed with an insight into current interceptive treatment modalities. © Litsas and Acar; Licensee Bentham Open.
Keywords: Diagnosis; Early displaced canines; Etiology; Prevention